2018
DOI: 10.1016/j.ccell.2017.11.019
|View full text |Cite
|
Sign up to set email alerts
|

TIM-3 Regulates CD103+ Dendritic Cell Function and Response to Chemotherapy in Breast Cancer

Abstract: Intratumoral CD103 dendritic cells (DCs) are necessary for anti-tumor immunity. Here we evaluated the expression of immune regulators by CD103 DCs in a murine model of breast cancer and identified expression of TIM-3 as a target for therapy. Anti-TIM-3 antibody improved response to paclitaxel chemotherapy in models of triple-negative and luminal B disease, with no evidence of toxicity. Combined efficacy was CD8 T cell dependent and associated with increased granzyme B expression; however, TIM-3 expression was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
268
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(276 citation statements)
references
References 68 publications
(97 reference statements)
7
268
1
Order By: Relevance
“…Several reports also highlight their importance in presenting tumor Ags to intratumor CTLs and in attracting CTLs to the TME (18)(19)(20). We found that depletion of pre-cDC-derived DCs in Zbtb46-DTR bone marrow chimeras abolished CTL proliferation and expansion in TDLNs, confirming their dominance in presenting tumor Ags in lymphoid tissues.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Several reports also highlight their importance in presenting tumor Ags to intratumor CTLs and in attracting CTLs to the TME (18)(19)(20). We found that depletion of pre-cDC-derived DCs in Zbtb46-DTR bone marrow chimeras abolished CTL proliferation and expansion in TDLNs, confirming their dominance in presenting tumor Ags in lymphoid tissues.…”
Section: Discussionsupporting
confidence: 60%
“…This interest has been bolstered by analyses of The Cancer Genome Atlas showing that patient survival for many cancers correlates positively with the gene expression signature for human DC1 (18,20,39). Whether this correlation relates to better priming of tumor Agspecific T cells in lymphoid tissues, the TME, or both has been difficult to discern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once primed, expression of CXCR3 by effector CD8 + T cells enables their recruitment into the tumor microenvironment (Mikucki et al, 2015), where in the absence of expression of inhibitory molecules, such as PD-1, they can mediate tumor destruction. This CD8 + T cell recruitment is thought to be largely controlled by CD103 + DCs at the tumor site, which have been shown to be the predominant source of the ligands CXCL9 and CXCL10 in multiple tumors (de Mingo Pulido et al, 2018; Spranger et al, 2017). Thus, via their control of multiple facets of the CD8 + T cell response, CD103 + DCs are a key determinant of the magnitude of the antitumor response, and understanding their regulation in tumor settings is of great therapeutic importance.…”
Section: Introductionmentioning
confidence: 99%
“…TIM-3 immunohistochemistry was conducted with anti-TIM-3 rabbit monoclonal antibody clone D5D5R from Cell Signaling (Cat# 45208) as employed in other publications 21,33,49,50 , here using a Ventana Ultra automated stainer (Ventana Medical Systems) in concordance with manufacturer’s protocol. In brief, slides underwent antigen retrieval with Standard Cell Conditioning 1 reagent (Ventana Medical Systems) followed by 60 minutes of primary antibody incubation (applied at 1:50 dilution) with no heat, and visualized using a chromoMap DAB detection kit (Ventana Medical Systems).…”
Section: Methodsmentioning
confidence: 99%